Particle mixing in bubbling fluidized bed reactors with continuous particle exchange. (23rd February 2019) - Hofer, G.; Märzinger, T.; Eder, C.; Pröll, F.; Pröll, T.
Highlights: Tracer experiment used for bubbling bed particle mixing characterization. Bubbling bed mixing mostly characterized by ideally mixed flow. Axial dispersion plug flow superimposes mixed flow at fluidization number of 4.7. Dead spaces and short-circuit flows observed at fluidization number of 4.7. Abstract: This paper reports on experiments conducted with a cold flow model utilized for the investigation of the particle residence time distribution and mixing characteristics in a bubbling fluidized bed with continuous solids exchange. The investigated system is of a rectangular cross section (0.4 × 0.2 m) with a bed height of 0.17 m. A measurement device based on an alternating current bridge circuitry coupled with lock-in amplifier technology was built in the scope of quantifying the solids residence time distribution, whereby a pulse-injected ferromagnetic tracer creates the input signal. The implementation of a profound mathematical routine ensures the reproducible calculation of the particles mean residence time and characteristic values describing particle mixing phenomena. Therefore, the E -curve was modeled by mathematical convolution of the exit age distributions available for an ideally mixed continuous stirred tank reactor and a plug flow reactor with axial dispersion. It is shown that the in-bed mixing is highly dependent on the fluidization rate as well as on the solids circulation rate. Albeit the lowest superficial gas velocity equals a fluidization number of 4.7, the formation of dead spaces and short-circuit flows was observed under these conditions. Axial dispersion coefficients in the range of 5 · 10 - 3 to 7 · 10 - 1  m 2  s −1 were obtained.